UPAYA PENINGKATAN KREATIVITAS DAN HASIL BELAJAR EKONOMI SISWA KELAS XI IS 5 MELALUI STRATEGI SELF QUESTIONING AND ANSWERING TEST DI SMA BERSAMA BERASTAGI KABUPATEN KARO - Silvi tabah hati (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2021)
Abstract: This study aims to analyze the implementation of the self-questioning and answering test strategy. This self-questioning and answering test strategy is expected to increase students' creativity in the teaching and learning process, so as to improve student economic learning outcomes at SMA Bersama Berastagi, Karo Regency. This research is a classroom action research conducted collaboratively with teachers in the field of study. who acts as an observer, where the researcher acts as a teacher of economics. The object of this research is the students of class XI IS 5 SMA Bersama Berastagi Karo Regency. This research consists of two cycles. The data collected relates to student learning creativity in the form of observation sheets and to see the improvement of student learning outcomes through the provision of tests. The data obtained were processed using percentage analysis and mean score.The results of the research in the first cycle, creativity and economic learning outcomes of students in learning with strategies are in good criteria, creativity which is still low is in the creativity indicator providing input to friends during discussions which has increased quite well. The learning outcomes obtained by the students averaged 69.85, with 20 students who completed from 33 students. In the second cycle, there has been an increase in both creativity and student economic learning outcomes. For students' learning creativity, it can be categorized into good and very good criteria, and for learning outcomes in the second cycle, an average of 81.06 students have been obtained with 28 students who have completed from 33 people who have completed.Based on the results of the study, the authors suggest to teachers and principals to be able to increase creativity and student learning outcomes at SMA Bersama Berastagi by using a self-questioning and answering test strategy combined with the provision of reinforcement and reward as an alternative in learning strategies.Keywords: Self questioning and answering test strategy, Creativity, Learning Outcomes.